2016
DOI: 10.1093/mnras/stw1303
|View full text |Cite
|
Sign up to set email alerts
|

AHerschel-SPIRE survey of the Mon R2 giant molecular cloud: analysis of the gas column density probability density function

Abstract: We present a far-IR survey of the entire Mon R2 GMC with Herschel − SP IRE crosscalibrated with P lanck − HF I data. We fit the SEDs of each pixel with a greybody function and an optimal beta value of 1.8. We find that mid-range column densities obtained from far-IR dust emission and near-IR extinction are consistent. For the entire GMC, we find that the column density histogram, or N-PDF, is lognormal below ∼10 21 cm −2 . Above this value, the distribution takes a power law form with an index of -2.16. We ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 52 publications
8
87
0
Order By: Relevance
“…Yan et al (2019) determined distances for 52 molecular clouds (purple), most of which are local and at high Galactic latitudes. In order to make a comparison, we rescaled the plot size of two adjacent molecular clouds, Rosette (1.46 pc) and Mon R2 (0.86 kpc), according to their masses (Williams et al 1995;Pokhrel et al 2016). The 5% systematic error is included in the error bars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al (2019) determined distances for 52 molecular clouds (purple), most of which are local and at high Galactic latitudes. In order to make a comparison, we rescaled the plot size of two adjacent molecular clouds, Rosette (1.46 pc) and Mon R2 (0.86 kpc), according to their masses (Williams et al 1995;Pokhrel et al 2016). The 5% systematic error is included in the error bars.…”
Section: Discussionmentioning
confidence: 99%
“…The sizes of the 11 molecular clouds (red circles) and two adjacent molecular clouds (purple), Rosette (1.46 kpc) and Mon R2 (0.86 kpc), are proportional to their masses. The masses of Rosette (Williams et al 1995) and Mon R2 (Pokhrel et al 2016) molecular clouds are rescaled with updated distances, and are 1.3 × 10 5 and 4.3 × 10 4 M respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moscadelli et al (2009) surrounded by dense gas clumps with masses of 1 − 65 M and kinetic temperatures of 15 − 30 K. Moreover, recent Herschel dust continuum and C 18 O observations by Rayner et al (2017) showed that the gas and dust in Mon R2 has a distinct hub-spoke geometry, with a central hub of protostars and dense cores that may be fed by several connected filaments. The column density probability distribution function from the Herschel observations also shows two power-law tails, suggesting both turbulent-and gravity-dominated regimes in Mon R2 (Schneider et al 2015;Pokhrel et al 2016).…”
Section: Mon R2mentioning
confidence: 99%
“…Even in the nearby MCs the N-PDFs show a considerable variety; Pokhrel et al (2016) for instance, reported that the power-law tail for some regions in the Mon R2 MC exhibits a break. In such clouds the tail at the high-density end can in fact be fitted with two power-laws.…”
Section: Compressional and Solenoidal Modes Of The Velocity Fieldmentioning
confidence: 99%